The Role of Health Administration, Nursing, and Laboratory Specialists in Enhancing Patient Care Quality in Jeddah's Healthcare System - Faarooq Hassan Abdullah Alzahrani; Ali Ahmad Mohammed Aqili; Ahmed Obaidan Abdullah AlMutairi; Turki Mousa Mohammed Alkadi; Fahad Mesfer Saeed Alghamdi; Mohammad Shar Abosawadah; Nassar Abdullah saeed Alzahrani; Ehab Mahmoud Abduljawad; Bander Ahmed Algarni; Hanadi Mohammed Khalawi (International Journal of Medical Toxicology and Legal Medicine, 2024)
This review tends to discuss health administration, nursing, and laboratory experts as the most vital factors in achieving excellence in patient care in Jeddah's healthcare system. The city of Jeddah is a large city in Saudi Arabia, which is facing a continuous rise in the demand for quality health care. Improvement in the quality of patient outcomes, effective operation, and better health care delivery has to be accomplished by these three disciplines working together. In this scenario, the health administrators guarantee an appropriate distribution of resources, strategic planning, and policy formulation, while the nurses are working in individual cares and acting in direct contact between the patient and health professionals. Laboratory specialists are of immense importance to diagnose the problem correctly and to come up with a treatment plan. Interdisciplinary integration by these professionals enables a more efficient model of health with holistic action, better decision-making, reduced delay in treatment, and increased patient satisfaction. Though these are the challenges in communication and continuous professional development, the potential for growth due to better collaboration and technological advancement is huge. This paper will, therefore, focus on how imperative the interdisciplinary cooperation will be in answering the future health needs of the population in Jeddah and in attaining long-term excellence in healthcare.